Research on Advanced Material Applications for Enhancing the Performance of New Energy Vehicle Components - Zengcong Wang (Innovation in Science and Technology, 2025)
This study aims to explore the application of advanced materials in new energy vehicle (NEV) components and assess their contribution to enhancing the overall vehicle performance. With the growing global demand for sustainable transportation solutions, NEVs have become a significant direction for the automotive industry. Against this backdrop, the performance enhancement of components is key to achieving higher energy efficiency, longer driving range, and a better driving experience. This paper first reviews the development history of new energy vehicle technology and the classification of advanced materials, then analyzes in detail the application of advanced materials in battery systems, electric motors and electronic control systems, lightweight structures, and thermal management systems. Through experimental research and case studies, this paper evaluates the specific impact of these materials on component performance and discusses the challenges faced in practical applications and future development directions. The research results show that the application of advanced materials can significantly enhance the performance of new energy vehicles, providing strong technical support for the further development of new energy vehicles. Finally, this paper proposes solutions to the challenges and limitations of performance enhancement in the application of advanced materials and suggests future research directions.